Determinants of the Issuance of Put/Call convertibles in the non-financial sector of the US market - Damian Kaźmierczak; Jakub Marszałek (Comparative Economic Research. Central and Eastern Europe, 2014)
The aim of this article is to characterize and show the differences between issuers of ordinary convertibles and convertibles with attached put/call provisions (put/call convertibles). The research was carried out on a sample of 379 firms in the US market, outside the financial sector, between 2002 and 2011. It turns out that the issuers of put/call convertibles are the companies with a higher risk exposure, associated with, inter alia, a higher level of indebtedness and worse ratio between the issue value to the fixed assets value. Adding the put/call provisions is aimed at decreasing issuers' risk exposure, which may increase the market demand for this type of convertible securities
Keywords: 330; financing; convertible bonds; put/call provisions; U.S market